2022
DOI: 10.1111/gcb.16074
|View full text |Cite
|
Sign up to set email alerts
|

Desert dust deposition supplies essential bioelements to Red Sea corals

Abstract: Coral reefs are in decline worldwide due to a combination of local (e.g. pollution and overfishing) and global (e.g. ocean warming and acidification) anthropogenic pressures (Heron et al., 2016;Kennedy et al., 2013). Among all threats, those associated with global ocean warming are the most severe, as rising seawater temperatures triggers repeated mass coral bleaching events in almost all of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 114 publications
1
8
0
Order By: Relevance
“…Alternatively, incubation in the dark did not allow symbionts to take advantage of the heterotrophic nutrients acquired by the host. A similar link between bleaching and symbiont starvation in trace elements and other essential nutrients was highlighted in previous studies (Ferrier-Pagès et al, 2018;Blanckaert et al, 2022). In these studies, providing the symbionts with essential metals (e.g.…”
Section: Discussionsupporting
confidence: 74%
“…Alternatively, incubation in the dark did not allow symbionts to take advantage of the heterotrophic nutrients acquired by the host. A similar link between bleaching and symbiont starvation in trace elements and other essential nutrients was highlighted in previous studies (Ferrier-Pagès et al, 2018;Blanckaert et al, 2022). In these studies, providing the symbionts with essential metals (e.g.…”
Section: Discussionsupporting
confidence: 74%
“…As a result, we believe that net air‐sea CO 2 exchange over the fringing coral reefs in the GoE is likely controlled by dust deposition into the low‐nutrient, low‐chlorophyll sea. The fertilization by dust may trigger an increase in metabolic processes in the reef ecosystems (Blanckaert et al., 2022) and to a lesser extent, in the adjacent ocean, resulting in a net exchange of CO 2 from the atmosphere to the ocean. Local meteorological conditions and their impact on water temperature may influence the magnitude of this air‐sea CO 2 exchange, but these impacts are likely secondary influences on the impact of dust.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations of the association between AOD (a proxy for dust concentrations) and air-sea exchange CO 2 indicate that such productivity may be related to marine fertilization by dust from the bordering deserts. For example, Blanckaert et al (2022) showed that dust deposited on the fringing coral reefs at IUI supplies nanomolar amounts of nitrate and essential bio-elements including iron, manganese, zinc, and copper from natural, industrial, and agricultural processes (Al-Taani et al, 2015) to the coral symbionts, thereby enhancing chlorophyll concentrations and photosynthesis. Dust fertilization may also trigger an increase in metabolic processes in the low-nutrient, low-chlorophyll coastal waters of the GoE without a corresponding increase in chlorophyll-a (biological productivity).…”
Section: Dust Deposition and Coral Reef Air-sea Co 2 Exchangementioning
confidence: 99%
“…The metal seascapes of coral reefs can be influenced by terrestrial forces at different geographical scales. Winddelivered (aeolian) dust is a significant source of soluble metals for Caribbean, Red Sea, and Pacific reefs (Jickells, 1999;Borchardt et al, 2020;Blanckaert et al, 2022). Metal contributions from dust input are frequently evaluated via Fe and aluminium (Al) inputs but aeolian dust is suspected to transport other trace elements (Measures & Vink, 2000).…”
Section: ) Abiotic Influences On Metal Seascapesmentioning
confidence: 99%
“…Specifically, the function and productivity of coral reef ecosystems relies on the symbiosis between reef-building corals and endosymbiotic dinoflagellate symbionts (Muscatine, 1990) from the family Symbiodiniaceae (Trench, 1979). Disequilibria within this partnership induced by changing metal abundance and stoichiometries can affect the physiology, growth, and calcification of reef-building corals (Ferrier-Pagès et al, 2001, 2005Shick et al, 2011;Metian et al, 2015;Hédouin et al, 2016;Ferrier-Pagès, Sauzéat & Balter, 2018;Biscéré et al, 2018a;Blanckaert et al, 2022). Less appreciated in comparison to the many studies on macronutrients [see reviews by D'Angelo & Wiedenmann (2014), Shantz & Burkepile (2014) and Morris et al (2019)] is that the family Symbiodiniaceae, and dinoflagellates in general, have higher metal requirements relative to other microalgae (Rodriguez et al, 2016;Reich et al, 2020a;Camp et al, 2022).…”
Section: Introductionmentioning
confidence: 99%